2018
DOI: 10.1002/bit.26823
|View full text |Cite
|
Sign up to set email alerts
|

Recurring genomic structural variation leads to clonal instability and loss of productivity

Abstract: Chinese hamster ovary cells, commonly used in the production of therapeutic proteins, are aneuploid. Their chromosomes bear structural abnormality and undergo changes in structure and number during cell proliferation. Some production cell lines are unstable and lose their productivity over time in the manufacturing process and during the product's life cycle. To better understand the link between genomic structural changes and productivity stability, an immunoglobulin G producing cell line was successively sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 55 publications
0
35
0
Order By: Relevance
“…Previous studies have characterized genomic variants across various CHO cell lines that may be a contributing factor to genome instability [ 9 11 ]. An unstable genome can result in reduced productivity in continuous cultures and fed-batch systems [ 12 , 13 ]. A common occurrence in both continuous cultures and fed-batch systems is the accumulation of metabolic waste products, such as ammonia and lactate.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have characterized genomic variants across various CHO cell lines that may be a contributing factor to genome instability [ 9 11 ]. An unstable genome can result in reduced productivity in continuous cultures and fed-batch systems [ 12 , 13 ]. A common occurrence in both continuous cultures and fed-batch systems is the accumulation of metabolic waste products, such as ammonia and lactate.…”
Section: Introductionmentioning
confidence: 99%
“…The undoubted advantages of immortalized CHO cells include a high proliferation rate, and the ability to adapt to genetic manipulations and culture conditions. At the same time, these properties are associated with an increased mutation rate, changes in the genome structure and DNA methylation pattern [ 7 9 ]. The karyotype heterogeneity of CHO cells increases with prolonged cultivation [ 10 ] and is inevitably reproduced in course of subcloning of cells [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…CHO cell line instability and its impact on cell line development remain a great challenge. In contrast to the genotypic instability for which the causes at the molecular level such as transgene loss or epigenetic regulations are well‐studied and characterized, very few studies have been reported on phenotypic instability. In this study, two clonal cell lines derived from Pfizer's SSI expression system were examined; both cell lines demonstrated genotypic stability, yet one exhibited an age‐related phenotypic instability (Cell Line A) and the other (Cell Line B) did not.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of expression in recombinant CHO cells has been extensively studied, and many groups have reported the loss of transgene copies or transcriptional silencing of promoters as the main causes. In contrast, there is minimal literature available on phenotypic instability.…”
Section: Introductionmentioning
confidence: 99%